Immunofluorescent patterns produced by antineutrophil cytoplasmic antibodies (ANCA) vary depending on neutrophil substrate and conjugate. Issue 9 (1st September 2002) - Pollock, W; Clarke, K; Gallagher, K; Hall, J; Luckhurst, E; McEvoy, R; Melny, J; Neil, J; Nikoloutsopoulos, A; Thompson, T; Trevisin, M; Savige, J
Abstract : Background: The "International consensus statement on testing and reporting antineutrophil cytoplasmic antibodies (ANCA)" advocates screening by indirect immunofluorescence (IIF), but external quality assessment programmes often demonstrate different IIF patterns for a single serum. Aim: To determine whether the variation in IIF patterns can be attributed solely to errors in interpretation. Methods: This study compared the IIF patterns produced by four sera (two with cytoplasmic or C-ANCA; one with perinuclear or P-ANCA with myeloperoxidase (MPO) specificity; and one P-ANCA without MPO specificity) that were tested in 11 different laboratories. The sera were examined according to individual laboratory protocols at dilutions of 1/10 to 1/40 using P1 (n = 4), P2 (n = 2), P3 (n = 2), or in house (n=3) neutrophil preparations and conjugates from manufacturers C1 (n = 3), C2 (n = 1), C3 (n = 2), C4 (n = 1), C5 (n = 2), and C6 (n = 2). The IIF patterns were noted in each laboratory, the testing repeated, and the fluorescent patterns photographed and subsequently discussed at a meeting of the Australian ANCA study group. Results: All IIF patterns described in individual laboratories were confirmed on retesting and by the ANCA study group. Neutrophil substrates produced commercially or in house varied in their ability to demonstrate cytoplasmic granularity and interlobular accentuation, which distinguish between "C-ANCA" and "C-ANCA (atypical)". All commercial and in house neutrophil substrates demonstrated neutrophil nuclear extension of P-ANCA fluorescence, which correlates with MPO specificity. However, eight assays (eight of 43) from eight laboratories resulted in IIF patterns different from those usually seen. One of these produced a C-ANCA (atypical) rather than a C-ANCA pattern. The other seven resulted in at least some cytoplasmic fluorescence when the consensus pattern was P-ANCA with (n = 4) or without (n = 3) MPO specificity. These assays used three different commercial and one in house neutrophil substrate, and six different conjugates, with anti-IgG, anti-(Fab)`2, anti-Ig (heavy and light chain), and anti-G, A, and M activity. Four of the seven assays tested on commercial substrates had used the manufacturer's conjugates. Conclusions: This study indicates that the variation in IIF patterns seen with ANCA positive sera tested in different laboratories does not necessarily result from errors in the interpretation of patterns and cannot be attributed solely to the use of a particular neutrophil substrate or conjugate, or to the use of substrate from one manufacturer and conjugate from another.